Viral DNA in bursal lymphomas induced by avian leukosis viruses. - Neiman, P (1980)
Avian leukosis viruses (ALV) induce malignant lymphoma of the bursa of Fabricius. Viral DNA in tumors and normal tissues from infected birds were analyzed by using restriction endonucleases. Viral DNA fragments diagnostic of the exogenous ALV were easily detected in tumors, uninvolved bursal tissue, kidney, and erythrocyte nuclei. Exogenous viral DNA was more difficult to detect in liver. Using a restriction endonuclease (SacI) which cleaves linear unintegrated ALV DNA in a single site to define integration sites in DNA from the various tissues, we were able to detect ALV DNA only in tumor tissue. We concluded that the proviral DNA detected in the various nontumor tissue must be integrated in multiple sites. The appearance of ALV integration sites uniquely in tumors suggests that they are clonal growths. Furthermore, the data suggested the presence of a single exogenous integration site for the ALV provirus in each of six early neoplastic bursal nodules. This provirus appeared to retain the organization of EcoRI and BamHI recognition sequences present in the genome of virus used to infect the birds. The ALV integration site appeared different in each of the tumors studied. In a widespread metastatic lymphoma, multiple ALV integration sites were found as well as structural alterations in at least some copies of the ALV provirus.